Microstructural and nonlinear electrical properties of ZnO ceramics with small amount of MnO2 dopant - Adnin, Noorfauzana; Zakaria, Azmi; Mohd Ghazali, Mohd Sabri; Wan Abdullah, Wan Rafizah; Hashim, Mansor (Penerbit Universiti Kebangsaan Malaysia, 2013)
A small amount of MnO2 dopant was added to ZnO system to see the improvement of the ceramic varistor microstructural and nonlinear electrical properties. The samples were prepared using solid-state reaction method and the microstructure and nonlinear electrical properties of the ZnO-xMnO2 system were investigated for × = 0.011 to 0.026 mol%, at three sintering temperatures, 1180°C, 1240°C and 1300°C for 1 and 2 h sintering time. The XRD and EDAX analyses showed that the main phase was ZnO while ZnMnO3 and ZnMnO7 as the secondary phases developed and distributed at the grain boundaries and triple point junction. The SEM observation revealed that prolonged sintering temperature and time improved the microstructure uniformity and strongly influences the nonlinear behavior of the samples. The maximum density and grain size have been observed at 92% of theoretical density and 10.8 μm, respectively and occur at the highest sintering temperature which is 1300°C. The value of nonlinear coefficient α is found to increase with the increase of MnO2 doping level up to 0.016 mol% and drop with further doping level increment for all sintering temperatures and time.